Cumprimento de obrigações de pagar em tutela provisória: técnicas para o cumprimento de decisões urgentes - Veiga, Daniel Brajal (2021)
The deadline to fulfill the urgent legal obligations to do or not to do something and the obligation to deliver something to someone is determined by the judge accordingly to the urgency of the situation, under penalty of a certain fine. This, however, does not occur with the fulfillment of the legal obligations to pay determined amount. The fulfillment of the obligations to pay a certain amount, regardless of the urgency of the situation, must occur in accordance with the proceeding pre-stablished by the lawmaker, that is, within 15 (fifteen) business days, under penalty of a fixed fine of 10% (ten percent) and attorney’s fees also fixed in advance of 10% (ten percent) on the amount of the obligation. Considering this fact, it is questionable if there is legal basis to justify the pre-stipulation of a deadline for the fulfillment of the urgent obligations whose object is to pay certain amount, specially taking into account what happens with the other obligations. The object of this study is to contribute and improve the enforcement of the urgent payment obligations proposing an application by similarity of what occurs with the other obligations, supported by other civil procedure institutes, in order to rule situations in which the creditor of the obligation cannot wait the debtor to fulfill his obligation. In short, the fulfillment of the obligation to pay, when there is urgency, shall be enforced in a deadline that avoids the occurrence of irreparable damages or damages whose reparation is extremely difficult